Antimicrobial Actions of Hexachlorophene: Lysis and Fixation of Bacterial Protoplasts - Corner, Thomas R. (1971)
Hexachlorophene was found to be both a lytic and a fixative agent for protoplasts isolated from Bacillus megaterium. Concentrations of 50 to 100 μg of drug per mg of original cell dry weight were required to lyse 4.4 × 10(9) protoplasts (2 mg of original cell dry weight). At higher drug concentrations, protoplasts became fixed against osmotic stress and reduced in sensitivity to disruption by n-butanol. Lower drug concentrations caused proportionate lysis in the protoplast population. Intact cells lost the ability to become plasmolyzed at these same hexachlorophene concentrations. Nonplasmolyzed, drug-treated cells were resistant to the action of lysozyme, whereas plasmolyzed, drug-treated cells were sensitive. But the sensitivity of isolated cell walls to lysozyme digestion was not markedly altered by hexachlorophene treatment. These effects appeared to be secondary in the killing of cells by hexachlorophene because they occurred at concentrations higher than the minimum lethal concentration.